1998
DOI: 10.1085/jgp.112.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Multiple Phosphorylation Sites in the Inactivation Particle of a K+ Channel

Abstract: Protein kinase C inhibits inactivation gating of Kv3.4 K+ channels, and at least two NH2-terminal serines (S15 and S21) appeared involved in this interaction (Covarrubias et al. 1994. Neuron. 13:1403–1412). Here we have investigated the molecular mechanism of this regulatory process. Site-directed mutagenesis (serine → alanine) revealed two additional sites at S8 and S9. The mutation S9A inhibited the action of PKC by ∼85%, whereas S8A, S15A, and S21A exhibited smaller reductions (41, 35, and 50%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…In such a hypothetical case, tyrosine phosphorylation on the ShB peptide would be equivalent to the reported serine phosphorylation on the inactivation peptide of the rapidly inactivating K v 3.4 channel (22,24), and thus, it could have important consequences on the regulation of neuronal excitability. Moreover, similarly to the observations reported here regarding the resemblance between the effects of tyrosine phosphorylation and the L7E mutation in the ShB peptide, mutation of serine residues to aspartates in the K v 3.4 channel was found to mimic the action of protein kinase C (23). In any case, there is increasing evidence to support the fact that certain potassium channels exist in vivo as a complex with the kinases and phosphatases that regulate them (48)(49)(50), and therefore, covalent modification of these channels by phosphorylation at different sites, including the ball domains, appears as a likely candidate to further increase the already diverse functional patterns exhibited by the complex K + channel superfamily.…”
Section: Discussionsupporting
confidence: 86%
“…In such a hypothetical case, tyrosine phosphorylation on the ShB peptide would be equivalent to the reported serine phosphorylation on the inactivation peptide of the rapidly inactivating K v 3.4 channel (22,24), and thus, it could have important consequences on the regulation of neuronal excitability. Moreover, similarly to the observations reported here regarding the resemblance between the effects of tyrosine phosphorylation and the L7E mutation in the ShB peptide, mutation of serine residues to aspartates in the K v 3.4 channel was found to mimic the action of protein kinase C (23). In any case, there is increasing evidence to support the fact that certain potassium channels exist in vivo as a complex with the kinases and phosphatases that regulate them (48)(49)(50), and therefore, covalent modification of these channels by phosphorylation at different sites, including the ball domains, appears as a likely candidate to further increase the already diverse functional patterns exhibited by the complex K + channel superfamily.…”
Section: Discussionsupporting
confidence: 86%
“…7,8,[12][13][14]17,18 Moreover, Kv3.4 siRNA nearly ablates the high voltageactivated K C current in small-diameter DRG neurons. 7 Although fast-inactivating slowing of macroscopic inactivation in DRG nociceptors under normal conditions (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…[12][13][14] Early reports showed modulation of fast Kv3.4 channel inactivation by oxidation, phosphorylation and PIP2 in heterologous expression systems. [15][16][17][18] Demonstrating that inactivation modulation also occurs in neurons, we showed that PKC activation dramatically slows inactivation of the native Kv3.4 channel expressed in DRG nociceptors. 7 Under physiological conditions, however, Kv3.4 channel inactivation is not modulated by PIP2.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This would convert a normally innocuous tactile stimulus turns into a noxious stimulus. In addition to reduced expression, I A s can also be suppressed if the channel becomes phosphorylated (Beck et al, 1998;Birnbaum et al, 2004;Sergeant et al, 2005). Phosphorylation of Kv4.2 in dorsal horn neurons has been proposed to underlie the induction of central sensitization, a cellular mechanism of neuropathic pain (Ji et al, 2003).…”
Section: Relationship Between A-channels and Nerve Ligation-induced Nmentioning
confidence: 99%